Education in Economic Theory - Jasmina Osmankovic; Hatidza Jahic; Ensar Sehic (Economic Review: Journal of Economics and Business, 2011)
This paper aims to show the evolution of the role and importance of education in economic theory, especially in theoretical approaches to economic development after World War II. In order to find answers and to present a current issue why and how certain countries have made progress while others have regressed in the development process, many theories and models explaining processes of growth and development have emerged and developed. By applying the method of analysis, synthesis and comparison, and based on earlier works, classification of theories of development has been made to analyze the evolution process of the role and importance of education in the development process. Presentation of the classification theory refers to: theories of economic development (the classical theory and contemporary models of development and underdevelopment) and theories of interdependence of education and development (theory of human capital, human development and approach to the returns on investment in education).This paper presents the basic settings, ideas and thoughts of the key authors of these theories and models and the role of education and human capital in these theoretical approaches. Research has shown that the analysis of interdependence of education and economic development has been the subject of interest of researchers for many decades and that today, taking into account the high degree of development of theoretical approaches, there is no full commitment to the classic theories nor there is a unified approach to endogenous growth, but an approach that promotes the elements of both, considering education as the key factor of development of the 21st century.
Keywords: I25; 330